Pemidanaan Tindak Pidana Narkotika dalam Perspektif Teori Kepastian Hukum - Yusyanto, Yusyanto; Fransisco, Fransisco; Murhaini, Suriansyah (Dinasti Research, 2025)
Money laundering or money laundering is a series of activities which is a process carried out by a person or organization against illicit money, namely money from criminal acts, with the intention of hiding, disguising the origin of the money from the government or the competent authority to take action against criminal acts by means of: other and especially include the money in the financial system so that the money can then be issued to the financial system as lawful money. Money laundering has now become a phenomenon in the world and also an international challenge. There is no universal and comparative definition of money laundering and many parties, both from the prosecution, crime investigation agencies, businessmen and companies, developed countries and third world countries each have their own definition of what is called money laundering based on different priorities and perspectives. Money laundering generally comes from criminal activities, one of which is narcotics crime. The approach method used in this study is a normative juridical approach. The research specifications used are normative descriptive, primary and secondary data sources and use qualitative analysis. This writing is analyzed. Problems are analyzed with the theory of legal certainty and the theory of justice